Remodeling Effects of the Combination of GGT Scaffolds, Percutaneous Electrical Stimulation, and Acupuncture on Large Bone Defects in Rats - Yao, Chun-Hsu; Yang, Bo-Yin; Li, Yi-Chen Ethan (Frontiers in Bioengineering and Biotechnology, 2022)
Regeneration defect of bone is a long-term physiological process after bone injuries. To accelerate the bone remodeling process, the combination of chemical and physical stimulations provides an efficient strategy to mature and to functionalize osteoclasts and osteoblasts. This study aims to investigate the dual effects of a tricalcium phosphate (TCP)-based gelatin scaffold (GGT) in combination with electroacupuncture stimulation on the activation of osteoclasts and osteoblasts as well as new bone regrowth in vitro and in vivo. We demonstrated that electrical stimulation changes the pH of culture medium and activates osteoblasts and osteoclasts in an in vitro co-culture system. Furthermore, we showed that electroacupuncture stimulation can enhance osteogenesis and new bone regrowth in vivo and can up-regulate the mechanism among parathyroid hormone intact (PTH-i), calcium, osteoclasts, and osteoblasts in the bone-defected rats. Those results showed the potential interest to combine electroacupuncture technique with GGT scaffolds to improve bone remodeling after injury.